Co-isolation of human donor eye cells and development of oncogene-mutated melanocytes to study uveal melanoma - Yunxi Chen; Eva Jin; Mohamed Abdouh; Éric Bonneil; Daniel Alexander Jimenez Cruz; Thupten Tsering; Qianqian Zhou; Aurélie Fuentes-Rodriguez; Alexandra Bartolomucci; Alicia Goyeneche; Solange Landreville; Miguel N. Burnier; et al. (BMC Biology)
Abstract Background Uveal melanoma (UM) is the most common intraocular tumor in adults, arises either de novo from normal choroidal melanocytes (NCMs) or from pre-existing nevi that stem from NCMs and are thought to harbor UM-initiating mutations, most commonly in GNAQ or GNA11. However, there are no commercially available NCM cell lines, nor is there a detailed protocol for developing an oncogene-mutated CM line (MutCM) to study UM development. This study aimed to establish and characterize premalignant CM models from human donor eyes to recapitulate the cell populations at the origin of UM. Results Given the precious value of human donor eyes for studying multiple ocular cell types, we validated a co-isolation protocol of both human NCMs and retinal pigment epithelial (RPE) cells from a single eye. To this end, NCMs and RPE cells were sequentially isolated from 20 donors, with success rates of 95% and 75%, respectively. MutCMs were generated from 10 donors using GNAQ Q209L -carried lentivirus with high mutant copies (up to 98.8% of total GNAQ copies being mutant). NCM growth and behavior were characterized under different culture conditions (i.e., supplementation with serum and 12-O-tetradecanoylphorbol-13-acetate) to determine optimized protocols. Particularly, Matrigel™ coating induced spheroid growth under certain coating thickness and cell seeding density but did not improve NCM metabolic activity. Current methodologies in NCM isolation, culture, and research applications were summarized. Proteomic profiling of 4 NCMs, 1 MutCM, and 3 UMs allowed to discover significant differences in UMs including a downregulation of proteins linked to melanocyte differentiation and an upregulation of proteins involved in RNA metabolism. RNA sequencing revealed enriched pathways related to cancer, notably PI3K-Akt and MAPK signaling pathways, in MutCMs and UM cells compared to NCMs, providing insights into molecular changes in GNAQ Q209L -mutated pre-cancer cell models and UM cells. Conclusions We successfully isolated and established NCM, RPE, and MutCM cell lines. We describe efficient methods for the isolation and growth of NCMs and report their phenotypic, proteomic, and transcriptomic characteristics, which will facilitate the investigation of UM development and progression. The co-isolated RPE cells could benefit research on other ocular pathologies, such as age-related macular degeneration. Graphical Abstract Created with https://www.biorender.com/ .